Manajemen Dakwah dalam Transformasi Sosial di Sukamaju Kota Bandung - Agi Muhammad Abdul Ghani; Mukarom, Zaenal; Abidin, Yusuf Zainal; Setiawan, Asep Iwan (Tadbir: Jurnal Manajemen Dakwah, 2025)
This research focuses on understanding the role of da'wah management in facilitating social transformation within Sukamaju Village and examining the impact of da'wah management on social change within the community. The study employs a case study methodology with a qualitative approach. Data were collected through field observations, interviews with several key informants, and various documents deemed significant for this research. The findings indicate that da'wah management plays a crucial role in the process of social transformation in Sukamaju Village, Bandung City. Through a systematic and planned approach, da'wah management not only serves as a medium for conveying religious information but also acts as a tool for empowering the community. The implications of effective da'wah management are the creation of a more empowered and self-sufficient society. With da'wah programmes focusing on economic empowerment, education, and health, the community of Sukamaju is better equipped to understand the importance of collaboration in achieving shared goals. Furthermore, da'wah management also contributes to fostering social awareness and concern among residents.